Factors influencing consumer decisions in halal tourism (case study Indonesia and Malaysia) - Sumardi, Retno Santi; Mukhamad Najib; Sarma, Ma'mun; Bali Mahomed, Anuar Shah (Faculty of Technology Management & Business, Universiti Tun Hussein Onn Maaysia, 2019)
Determining consumer decisions in halal tourism is vital as the Muslim population continues to increase in the world. Tourism sector plays a significant role in the economy of a country. Therefore, this research aimed to analyze factors such as environment, individual, attitude, and motivation toward a decision on halal tourism, and the dominant factors influencing consumer decision in halal tourism. It was a quantitative analysis that used a survey on Muslim traveler who has been visiting both Malaysia and Indonesia. The study collected data from both Malaysian and Indonesian. Kuala Lumpur was selected to represent Malaysia, while Lombok was chosen to represent Indonesia. The results were analyzed through Structural Equation Modelling (SEM). Based on the characteristics of the respondent, the majority of consumers in halal tourism are women, both single or married, with an age range between 18-40 years with upper income and university level education. In the result, the factors influencing Indonesian consumer decisions in halal tourism were the environmental factor (situation) and the differences of an individual (personality). For Malaysian consumer, attitude (knowledge) was the factor influencing the decision in halal tourism.